2006
DOI: 10.2193/0091-7648(2006)34[936:baccrp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Butterflies and Continuous Conservation Reserve Program Filter Strips: Landscape Considerations

Abstract: Filter strips or buffers are areas of grass or other perennial herbaceous vegetation established along waterways to remove contaminants and sediments from agricultural field runoff. In the heavily cultivated regions of the Midwestern United States, these buffer zones established under the Farm Bill provide important habitat for wildlife such as butterflies. The question of how the landscape context of these plantings influences their use has not been adequately researched. We used multiple regression and Akaik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In 2008 pollinators became a high priority wildlife taxon for CRP projects 223 . Butterflies benefit from CRP restorations, but there have not yet been any studies of CRP effects on bees 226 . The practice of sowing CRP restorations with nonnative grasses is widespread 225 and likely diminishes the value of these habitats for bees.…”
Section: Restoring Bee Communitiesmentioning
confidence: 99%
“…In 2008 pollinators became a high priority wildlife taxon for CRP projects 223 . Butterflies benefit from CRP restorations, but there have not yet been any studies of CRP effects on bees 226 . The practice of sowing CRP restorations with nonnative grasses is widespread 225 and likely diminishes the value of these habitats for bees.…”
Section: Restoring Bee Communitiesmentioning
confidence: 99%
“…In Iowa, the USA's top producer of corn (Zea mays) and soybeans (Glycine max), the current agricultural landscape is dominated by row crop monocultures, and more than 99% of the state's tallgrass prairie habitat has been destroyed (Samson and Knopf 1994). In this context, butterfly populations persist in fragmented prairie remnants (Davis et al 2008;Davis et al 2007;Vogel et al 2007), in linear grassland habitats along crop fields, fence rows, roadsides (Ries et al 2001), and waterways (Reeder et al 2005;Davros et al 2006), and in prairie reconstructions (Shepherd and Debinski 2005). These currently available grassland habitats are small, isolated, and generally of lower quality (i.e., less floristically diverse, subject to exotic and woody plant invasions, possessing altered disturbance regimes, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Bumble bee populations respond positively to the presence of unmanaged areas (pastures, meadows, and forests) that provide nesting and forage sites (Williams 1986). Davros et al (2006), working with similar Conservation Reserve Program habitats, reported that butterfly densities and species are affected by habitat fragmentation. Delta Junction has large areas devoted to the Conservation Reserve Program with minimum disturbance (Seefeldt et al 2010) that might have contributed to the higher bee densities there.…”
Section: Discussionmentioning
confidence: 99%